Pricing Uncertainty Induced by Climate Change. (14th February 2020) - Barnett, Michael; Brock, William; Hansen, Lars Peter
Abstract: Geophysicists examine and document the repercussions for the earth's climate induced by alternative emission scenarios and model specifications. Using simplified approximations, they produce tractable characterizations of the associated uncertainty. Meanwhile, economists write highly stylized damage functions to speculate about how climate change alters macroeconomic and growth opportunities. How can we assess both climate and emissions impacts, as well as uncertainty in the broadest sense, in social decision-making? We provide a framework for answering this question by embracing recent decision theory and tools from asset pricing, and we apply this structure with its interacting components to a revealing quantitative illustration.